Performance Effectiveness of the Land Agency in Issuing Land Rights Certificates and its Impact on Regional Income Banjarbaru City - Adwin Tista; Ahmad Yunani; Noor Rahmini (Journal of Social Research, 2026)
The research aims to determine the effectiveness of the performance of the Banjarbaru city land agency in issuing land rights certificates; know the supporting and inhibiting factors; knowing the impact on regional income of the city of Banjarbaru and efforts to increase the effectiveness of the performance of the land agency of the city of Banjarbaru in issuing certificates of land rights. The research method was an analytical descriptive method with a qualitative descriptive approach. The research model is Geertz Interpretive namely the approach by looking for "meaning" not looking for law. The results of the study show that the effectiveness of the performance of the Banjarbaru City Land Agency in Issuing Land Rights Certificates in 2022 is effective, but performance is still not optimal due to service discrimination , contribution - oriented , difficult and convoluted in the process of issuing land rights certificates, delays issuance of certificates, lack of accountability due to non-transparent issues of cost and time in issuing certificates,  supporting inhibiting factors. Issuance of Land Rights Certificates in 2022 will have an impact on the original regional income of the city of Banjarbaru. Efforts to increase the effectiveness of performance in issuing certificates of land rights by maximizing the computerized system, there is guidance and training for land agency apparatus, effective the mediation system, strengthen human resources and continue the PTSL program as well as collaboration with the local government, police, prosecutors and the military